Type classification and contiguous protection: Analysis of traditional village cultural landscape in Tongjiang county, China - Cai Pengcheng; Ubong Imang (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2025)
Traditional village cultural landscape is a witness to the historical and cultural heritage of the villages and an important part of the protection of rural cultural heritage. This study explores the type classification of 37 traditional villages in Tongjiang County from the perspective of cultural landscape. The data of the traditional village clusters in Tongjiang County were collected by using the observation method and the secondary data method, and the data were analyzed by using the content analysis method to construct a research system for the classification of traditional village types. The research results show that: According to the prominent characteristics of the cultural landscapes of traditional villages in Tongjiang County, they can be classified into five categories: agricultural landscape, traditional architecture, revolutionary relics, humanistic history, and folk customs and religious culture. Based on the characteristic cultural landscape resources of different types of traditional village es, a concentrated and contiguous sustainable development model that conforms to the characteristics of the villages is proposed. This study, by classifying traditional villages into types, provides practical inspirations for the classified protection of traditional village groups in counties, and offers countermeasure references for the concentrated and contiguous protection of traditional village cultural landscape and the implementation of the rural revitalization strategy.